PERAN ICE BREAKING DALAM MEMBANGUN INTERAKSI POSITIF ANTARA GURU DAN SISWA DI KELAS BAWAH: STUDI KASUS KELAS III SDN CIWEDUS - Ruaida, Ruaida; Desty Endrawati Subroto; Nabila, Nabila (Cahaya Ilmu Bangsa Institute, 2025)
This study explores the role of ice breaking in building positive interactions between teachers and students in the third grade of SDN Ciwedus using a descriptive qualitative approach. Data collection was conducted through participatory observation of 12 learning sessions, semi-structured interviews with teachers and the principal, focus group discussions with students, and analysis of learning documents. The results revealed that structured and contextual implementation of ice breaking contributes significantly to the transformation of educational interaction patterns into more collaborative and dialogical ones. Ice breaking was implemented at three strategic times (beginning of learning, transitions between materials, and during attention decreases) with a predominance of kinesthetic-based activities (42%). After ice breaking implementation, there was an identified increase in cognitive attention (89% of students), positive affective expression (94%), and more proactive interactive behavior (68%). Implementation constraints included time limitations, heterogeneity of student responsiveness, and challenges in maintaining relevance to learning substance. Adaptation strategies developed by teachers included integration of ice breaking as a pedagogical instrument and development of categorized activity banks. This study concludes that ice breaking plays a strategic role in forming a conducive learning ecosystem in lower grades, not only creating a pleasant atmosphere but also facilitating fundamental transformation in teacher-student relational dynamics.